Analisis Kesulitan Membaca Al-Quran di Kalangan Mahasiswa Pendidikan Teknik Mesin UPI Angkatan 2024 - Solihin, Ahmad; Lazhwardi, Rayyana; Noviana, Rivana; Munawar, Wahid; Jenuri, Jenuri (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study aims to analyze the factors contributing to difficulties in reading the Quran among students of the Mechanical Engineering Education program at Universitas Pendidikan Indonesia (UPI), class of 2024. Various barriers, such as limited formal religious education, lack of practice time, and an academic focus centered on technical fields, often lead to neglect of spiritual development. The study employs a quantitative approach with a survey method, gathering data through an online questionnaire that addresses students' reading frequency and the challenges they face. Findings reveal that most students spend 5-15 minutes daily reading the Quran, with the primary challenge being the application of tajweed rules. Based on these findings, the study recommends intensive guidance and motivational programs to improve students' Quran reading skills. Face-to-face instruction is considered essential for addressing technical difficulties, while campus-supported motivational programs can foster greater student interest.